2007
DOI: 10.1007/s12016-007-8018-1
|View full text |Cite
|
Sign up to set email alerts
|

Does the Presence of Anti-CCP Autoantibodies and Their Serum Levels Influence the Severity and Activity in Rheumatoid Arthritis Patients?

Abstract: This study aims to investigate the association of the presence and of the titer of autoantibodies against cyclic citrullinated peptides (aCCP), with clinical manifestations and disease activity in a cohort of patients with rheumatoid arthritis (RA). From January 2000 through December 2005, 135 patients were diagnosed with RA at the Rheumatology Unit of our hospital. Demographic, clinical, laboratory, and therapeutic parameters were evaluated in all patients at study entry and at every follow-up visit. Positivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 27 publications
4
11
1
1
Order By: Relevance
“…Our results revealed that RF tended to be positive in ACPA positive patients. These results were previously reported by Nishimura et al 19 , Papadopoulos et al 20 and Onder et al 21 . The present study showed strong relationship between disease activity and ACPA titer as it showed higher levels in RA patients with severe disease activity & low levels in patients with mild disease activity, this agrees with the results of Papadopoulos et al, (20) & Onder et al 21 , showed that the majority of ACPA + ve patients exhibited more active disease with higher DAS 28 score 22 .…”
Section: Discussionsupporting
confidence: 90%
“…Our results revealed that RF tended to be positive in ACPA positive patients. These results were previously reported by Nishimura et al 19 , Papadopoulos et al 20 and Onder et al 21 . The present study showed strong relationship between disease activity and ACPA titer as it showed higher levels in RA patients with severe disease activity & low levels in patients with mild disease activity, this agrees with the results of Papadopoulos et al, (20) & Onder et al 21 , showed that the majority of ACPA + ve patients exhibited more active disease with higher DAS 28 score 22 .…”
Section: Discussionsupporting
confidence: 90%
“…Titles of CCP2 on average tended to be lower than the third generation techniques. We observed high values (on average > 500 IU/dL) with the three techniques, higher than those reported in publications by Lee et al 54 and Papadopoulos et al, 55 two of the few studies on absolute titles of anti-CCP and its correlation with disease progression.…”
contrasting
confidence: 70%
“…There is considerable disagreement about the relationship between anti-CCP positivity and DAS-28 scores in RA patients (26)(27)(28)(29). In this study, DAS-28 scores and serum RF positivity were found to be associated with anti-CCP positivity.…”
Section: Discussionmentioning
confidence: 53%
“…Despite the view of anti-CCP is a reliable diagnostic and prognostic indicator, its relationship with the activity and severity of the disease is unclear (18). Anti-CCP has been reported to be better than RF, to predict the disease activity over 3 years.…”
Section: Discussionmentioning
confidence: 99%